Dinamika Agenda Setting dan Formulasi Kebijakan untuk Pembangunan Berkelanjutan: Analisis Bibliometrik - Permatasari, Indah; Putra, Raniasa (Universitas Muhammadiyah Mataram, 2024)
This study examines the dynamics of agenda setting and policy formulation for Sustainable Development Goals (SDGs) using bibliometric analysis. Data sourced from Google Scholar covering the period 2019-2023, employing SDGs-related keywords. Network Visualization Co-Occurrence analysis reveals patterns of relationships among concepts, while Overlay and Density Visualizations provide additional context and levels of interconnectedness. Results indicate clusters encompassing sustainable business adoption, urban development, and the impact of COVID-19. Co-Authorship analysis identifies key authors such as Filho, W Leal, and Li, Y. The conclusion presents profound insights into SDGs literature and recommends further research on specific aspects.